In Vivo Monitoring of Glycerolipid Metabolism in Animal Nutrition Biomodel-Fed Smart-Farm Eggs - Victor A Zammit; Sang O Park (Foods, 2024)
Although many studies have examined the biochemical metabolic pathways by which an egg (egg yolk) lowers blood lipid levels, data on the molecular biological mechanisms that regulate and induce the partitioning of hepatic glycerolipids are missing. The aim of this study was to investigate in vivo monitoring in four study groups using an animal nutrition biomodel fitted with a jugular-vein cannula after egg yolk intake: CON (control group, oral administration of 1.0 g of saline), T1 (oral administration of 1.0 g of pork belly fat), T2 (oral administration of 1.0 g of smart-farm egg yolk), and T3 (oral administration of T1 and T2 alternately every week). The eggs induced significant and reciprocal changes in incorporating 14C lipids into the total glycerolipids and releasing 14CO2, thereby regulating esterification and accelerating oxidation in vivo. The eggs increased phospholipid secretion from the liver into the blood and decreased triacylglycerol secretion by regulating the multiple cleavage of fatty acyl-CoA moieties’ fluxes. In conclusion, the results of the current study reveal the novel fact that eggs can lower blood lipids by lowering triacylglycerol secretion in the biochemical metabolic pathway of hepatic glycerolipid partitioning while simultaneously increasing phospholipid secretion and 14CO2 emission.